PENGARUH SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) TERHADAP EFEKTIVITAS KERJA PELAYANAN FISIOTERAPI DI RSUD KESEHATAN KERJA - Ratih Nurlatipah; Ai Susi Susanti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study is to see how the hospital management information system (SIMRS) affects the efficiency of physiotherapy at RSUD Kesehatan Kerja. The research approach employed is quantitative. Observation, questionnaires, interviews, and documentation studies were utilized to collect data. The total population is 5 respondents, namely physiotherapy officers and doctors Sp. KFR, and the sample used was 5 respondents using a sampling technique, namely saturated sampling. The results of this study showed a Spearman Rank correlation value of 0.975, which means the level of relationship between the variables of the hospital management information system (SIMRS) on the work effectiveness of physiotherapy services is between the intervals of 0.79 - 0.99 or a very strong relationship. Meanwhile, the effect of SIMRS variable (X) on variable (Y) work effectiveness of physiotherapy services is 95%. The study's findings indicate that hospital management information systems have an impact on the effectiveness of physiotherapy services at RSUD Kesehatan Kerja.